2019
DOI: 10.1108/ijccsm-04-2017-0084
|View full text |Cite
|
Sign up to set email alerts
|

Synergizing climate change mitigation and adaptation in Cameroon

Abstract: Purpose -This paper aims to examine the policy environments, institutional arrangements and practical implementation of some initiatives undertaken by the Government of Cameroon, together with some relevant stakeholders, in addressing climate change mitigation and adaptation at various levels in the country, which are prerequisites to promote synergistic ways of addressing climate change mitigation and adaptation.Design/methodology/approach -Using a qualitative approach to data collection, the paper draws upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The sectors with the most synergies were green urban infrastructures, construction, energy efficiency, and buildings. Another study used a qualitative method to examine the policy implementation of Cameroon’s climate mitigation and adaptation initiatives (Ngum et al 2019 ). While several policies address climate change, the findings indicated that they are all focused on mitigation rather than adaptation.…”
Section: Interrelationships and Synergies Between Adaptation And Miti...mentioning
confidence: 99%
“…The sectors with the most synergies were green urban infrastructures, construction, energy efficiency, and buildings. Another study used a qualitative method to examine the policy implementation of Cameroon’s climate mitigation and adaptation initiatives (Ngum et al 2019 ). While several policies address climate change, the findings indicated that they are all focused on mitigation rather than adaptation.…”
Section: Interrelationships and Synergies Between Adaptation And Miti...mentioning
confidence: 99%
“…Emerging economies possessed strong synergy potential, which might be associated with better capacity being available and/or potential for shaping their global images due to their growing emissions (Duguma et al 2014b). This analytical framework was applied by Ngum et al (2019) to look at efforts made by the Government of Cameroon and other stakeholders to promote synergies between climate change mitigation and adaptation. The authors concluded that policies, laws, strategies and institutional arrangements relevant to promoting an integrated approach to climate change were insufficient in Cameroon, but that some promising projects and activities existed that harnessed great potential for synergies.…”
Section: Synergies and Trade-offs Between Adaptation And Mitigationmentioning
confidence: 99%
“…In order to implement effective adaptations that will address the complex internal and external issues of climate change, multiple stakeholders should be engaged [16]. Studies show that multi-stakeholder groups have a more experienced understanding of various biophysical and socioeconomic conditions than individual entities, and that they are valuable knowledge bearers of potential adaptation options [17]; therefore, the engagement of multiple stakeholders at multiple levels could help us to identify locally-relevant aspects of climate change vulnerability and viable adaptation options to combat the impacts of climate change. Through a review of the most recent programs and policies for climate adaptation by the Chinese government, and the incorporation of the latest domestic and international scientific literatures, the major goals of this paper are: to highlight the utility of using multi-stakeholder groups for the development of regionally appropriate adaptation campaigns for agriculture; to explore what is already being done in China's agricultural sector; to identify barriers to action; and to examine the future expectations held by governments, researchers, and farmers.…”
Section: Introductionmentioning
confidence: 99%